(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted illumination of problem of forming of professionalism for future engineers-teachers on the basis of the personality-oriented approach. It is necessary to examine reformation of engineer-pedagogical education from point offorming of personality, rich in content and technological aspects.